Using the Linear Programming in Mediterranean Forest Management : A Study Case from the North of Morocco - Maadidi, Tayeb El; Aboudi, Ahmed El; Aid, Hlal El (International Journal of Scientific Research in Biological Sciences, 2022)
The multiple uses of Moroccan forest, the social context, and the limitation of traditional management methods makes it necessary to develop a new management method for forest management in Morocco. Therefore, the forest needs to be managed efficiently for multiple purposes. The present study consists of developing a new management approach for Moroccan forests. This approach will be based on a linear programming model to provide an optimal solution to the current forest management problems. The relevance of the approach and its various components requires a prerequisite for the computerization of forest management in Morocco. This method will be applied to the pine forests in the Oued Laou watershed. The forest is located in the North of Morocco and contains three artificial plantations that are Aleppo pine, Maritime pine, and Monterey pine. They occupy 104 Hectares, 41 Hectares, and 349 Hectares, respectively. To solve the linear programming model, 28 scenarios will be defined for all forests based on harvesting age, silviculture, and a planning horizon for the next 100 years, divided into 20 planning periods of 5 years. The new model should satisfy a maximum of timber production while respecting various management constraints, including land availability, forest normality, sustainable timber volume, and the legal right of grazing. The optimal solution guarantees a volume of wood production equal to 105.753 m3 while preserving the legal right of grazing. The irregular structure of forests will then be converted into a regular one.